Adolescents and young adults and mother-to-child transmission of HIV (Research, Society and Development, 2021)
Objective: To describe the profile of pregnant adolescents and young adults living with HIV/Aids notified in a reference hospital for infectious diseases in the state of Goiás and analyzing how characteristics related to the mother-child transmission of HIV in this population. Methodology: Cross-sectional study conducted with data extracted from forms of mandatory notification of investigation of children exposed to HIV. Variables were considered: age, municipality of origin and maternal education, use of antiretroviral drugs by the pregnant and the newborn, type of parturition (vaginal or cesarean) and breastfeeding. Results: Of the 157 pregnant living with HIV/Aids, 27,39% (n = 43) were adolescents and 72,61% (n = 114) young adults. The profile of this population indicate to the largest procedure outside the capital of Goiás, low education level and following the recommendations of the Ministry of Health regarding the use of antiretroviral during pregnancy and parturition. Of the children exposed to HIV, 5,09% (n = 8) became infected through mother-to-child transmission. The children's infection was the result of different combinations of not adopting the preventive measures recommended by national protocols. Conclusion: There was no study predominantly of young adult pregnant with low education level living with HIV/Aids. Belonging to the group of pregnant adolescents or young adults did not influence the taking of prophylactic measures for mother-to-child transmission of HIV. Do not to use antiretroviral drugs either at parturition or during pregnancy and breastfeeding were risk factors for mother-to-child transmission of HIV, while cesarean parturition proved to be a protective factor for most cases.